Operationalizing Occupation-Centered Education: Exploring the Subject-Centered Integrative Learning Model in Academic Education. - Brown, Addy; Hooper, Barbara; Barth, Devin; Zorn, Amanda (American Journal of Occupational Therapy)
Date Presented 4/1/2017 The purpose of this study was to explore the usefulness of the Subject-Centered Integrative Learning Model for academic educators developing occupation-centered practices. The model was found to guide the educators and has the potential to shape occupational therapy education. Primary Author and Speaker: Addy Brown Additional Authors and Speakers: Barbara Hooper, Devin Barth, Amanda Zorn